DETERMINAN NILAI PERUSAHAAN PUBLIK DI INDONESIA DAN MALAYSIA DENGAN KEPEMILIKAN INSTITUSI SEBAGAI VARIABEL PEMODERASI - Aulia Lathifa; Nurmala Ahmar; JMV. Mulyadi (POLITEKNIK LP3I JAKARTA, 2018)
Abstract Firm value is one the management's standard in managing the business. This study examines effect of financial factors such as profitability proxied by ROA, ROE, NPM, solvency proxied with DAR, DER, Institutional Ownership as moderator and the impact to firm value proxied by PBV in Indonesia and Malaysia for 2012 to 2016. Sampling used consisting of 51 companies, 26 companies from Indonesia and 25 companies from Malaysia for 5 years observation with total data 255 samples. Analytical technique using WarpPLS 6.0 and difference test using Multi Group analysis. Result shows profitability have significant positive effect to firm value in Indonesia, whereas in Malaysia has not effect to firm value. Solvency shows do not affects for both countries. Institutional ownership has significant positive effect in Indonesia nevertheless has no effect in Malaysia. Institutions found not able to moderate the effect of profitability and solvency in Indonesia, contrary result in Malaysia are found as pure to moderate effect of profitability to firm value and be a homologer to moderate effect of solvency to firm value. Different test effect shows there’s a significant difference effect of profitability to firm value in both countries whereas there is no difference effect of solvency to firm value.